The Changing Roles of the Building Guild in Construction, Maintenance, and Conservation of Earth Buildings: A Case Study - Theophilus A. Shittu (Buildings)
A guild is an association of artisans or merchants that oversee their craft or trade within a particular territory. In many cultures, building guilds have played a major role in the realisation and maintenance of earth buildings, as well as in the standardisation and dissemination of skills in the building trade. Zaria, in northern Nigeria, is one such traditional settlement where an earth building guild (magina) once played these key roles. Although the guild still exists and traditional titles are still bestowed to members of the guild, its role has changed significantly. Causes for this change are multifaceted but related, as identified during the fieldwork. The aim of this article is to present findings on the changing roles of the earth building guild (magina) in Zaria and how this change is affecting both the practice of earthen architecture and conservation of earth buildings in the city. This study began in 2021 whilst working on a conservation of earth building in Zaria, which involved the engagement of traditional builders (magina) from Zaria, led by Katukan Magina (deputy chief builder) and a member of the earth building guild from Djenne, Mali (Boubacar Kouroumanse). A deeper interest in the Zaria building guild ensued, which led to the further research presented in this article. The review of the existing literature provided a historical background to the Zaria building guild (magina). A comparative analysis of the literature and data generated from interviews and condition surveys were use for the identification of the changes that occur over time. Similarly, a proposal for positive change within the building guild was proposed using an example of a UNESCO World Heritage Site.